Using Patient-Reported Outcome Measures for Improved Decision-Making in Patients with Gastrointestinal Cancer – the Last Clinical Frontier in Surgical Oncology? - Søreide, Kjetil; Søreide, Annbjørg H. (Frontiers in Oncology, 2013)
The genomic era has introduced concepts of ‘personalized medicine’ and ‘targeted therapy’ in the field of oncology. Medicine has become increasingly complex with a plethora of potential dilemmas in diagnosis, treatment and management. The focus on classical outcomes for clinical decision-making is now increasingly being replaced by patient-reported outcome measures (PROMs). PROMs should increasingly now be in the center of patient-centered decision-making, based on valid, reliable and clinically useful measures delivered directly by the patient to the caregiver. Surgeons' ability to interpret and apply PROMs and QoL results must improve by education and further research, and has an unreleased potential to contribute to a better understanding of the patients' well-being. A number of caveats must be addressed before this can be brought to fruition; standardization for valid items; appropriate use of instruments; correct timing of the application; missing data handling, compliance and respondent drop-outs are but a few issues to be addressed. Based on the apparent lack of use in both research and clinical work, it should call for an educational effort to address this among surgeons caring for patients with cancer.